Mineral composition of poultry litter and its use in vineyeard fertilization - Miele, Alberto; Milan, Paulo Anísio (Pesquisa Agropecuaria Brasileira, 2014)
Chemical analysis of poultry litter were done in samples collected from 25 aviaries located in Garibaldi, state of Rio Grande do Sul. The objective was to know its mineral composition, having in view its use in vineyard fertilization. The levels of ten chemical elements, humidity and pH were determined. The values found were 3.02% of N, 1.32% of P, 2.38% of K, 2.19% of Ca, 0.52% of Mg, 0.33% of Fe, 0.89% of Na, 228 ppm of Zn, 80 ppm of Cu, and 299 ppm of Mn, in relation to the dried material. The humidity was 51.6% and the pH 7.7.